Relationship between Knowledge Level and Efforts to Control Blood Pressure in Hypertension Patients in the Work Area of Karangmulya Health Center, Karangpawitan District, Garut Regency - Neng Sunarti; Iin Patimah (Science Midwifery, 2018)
Hypertension is one of the common health problems. People with hypertension must be able to control their blood pressure to avoid serious diseases such as stroke, heart failure, kidney failure and other chronic diseases. To avoid seious status, good knowledge is needed. Controlling blood pressure is the key to success for all people with hypertension to prevent severe increases in blood pressure. This research uses descriptive correlation method. This research was conducted in the district Karangmulya Garut. Population is all people hypertension in the Karangmulya working area of ​​the district. The sample was determined by the Non Probability Sampling technique, quota sampling. The sample of the study was 57 respondents. The results showed that more than half of the respondent had a good level of knowledge which was as much as 70.2%. More than half of the sufferers in the Karangmulya Community Health Center work to prevent recurrence of hypertension that has remained as much as 57.9%. From the results of statistical tests obtained p value 0.00 (<0.05), with a correlation coefficient (r) of 0.609 which means that there is a significant relationship between the level of knowledge about hypertension and prevention of recurrence in patients with hypertension. Given that there are several findings in the study and limitations in this study, it is expected that in the future various parties can examine other factors related to the level of knowledge about hypertension and efforts to prevent recurrence in patients with hypertension, excluding the factors discussed in this study.